The Effect of Heating Temperature on the Antioxidant Activity of Red Rose Water Distillation Waste (Rosa damascena Mill) Using Varying Distillation Methods: Pengaruh Suhu Pemanasan terhadap Aktivitas Antioksidan Limbah Penyulingan Air Mawar Merah (Rosa damascena Mill) Dengan Variasi Metode Destilas - Ni putu cahya putriyani Cahya; Nanik Suhartatik; Yannie Asrie Widanti (Agrobiotek, 2024)
Red rose (Rosa damascena Mill) is one of the plant that can be easily found in Indonesia. The corolla of red roses contains natural dyes, namely anthocyanins which can be used as food coloring and the function as antioxidants or counteract free radicals. The corrola of red roses is used as a raw material in distillation of rose water. Rose water distillation poduces is a dark red liquid. This liquid waste has not been utilized optimally. Therefore, that further research is needed to determine the chemical content in it. So that the expected outcome of this research is the best chemical and sensory analysis of red rose water distillation waste based on it's antioxidant activity. The research design used a 2 factor factorial completely randomized design (CRD). The first factor is the variation of the distillation method while the second factor is the heating temperature of the red rose water waste (heated waste). The optimal treatment result was a combination of steam distillation method variations and 70Â°C heating temperature with following results obtained : 77,32% RSH DPPH, 61,02% FRAP value, 71,20 mg/g vitamin C, 4,58 mg total phenol.GAE/ g, pH 4,15, anthocyanin 121,93 mg/g, brightness 27,23 (*L), red-green chromatic 7,13 (*a), blue-yellow chromatic 7,54 (*b). Sensory analysis of color was 4.36 (deep red), other scents were 2.47 (slightly sour), rose aroma was 3.64 (strong), and overall preference was 3.75 (liked).